2021
DOI: 10.3389/fonc.2021.598320
|View full text |Cite
|
Sign up to set email alerts
|

Loosening Neuro-Optic Structures Dosimetric Constraints Provides High 5-Year Local Recurrence-Free Survival With Acceptable Toxicity in T4 Nasopharyngeal Carcinoma Patients Treated With Intensity-Modulated Radiotherapy

Abstract: ObjectiveWhether the original dosimetric constraints of neuro-optic structures (NOS) are appropriate for patients with nasopharyngeal carcinoma (NPC) undergoing intensity-modulated radiotherapy (IMRT) remains controversial. The present study compared the survival rates and radiation-induced optic neuropathy (RION) occurrence between T4 NPC patients whose NOS were irradiated with a near maximum dose received by 2% of the volume (D2%) >55 Gy and ≤55 Gy. Moreover, the NOS dosimetric parameters and their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In total, 74 studies described a retrospective study design, and 4 studies described a prospective study design. Four studies distinguished two groups in the study population according to the tumor type or radiation therapy technique [ 19 , 20 , 21 , 22 ]. Therefore, we divided these studies and analyzed the subgroups as separate study groups.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 74 studies described a retrospective study design, and 4 studies described a prospective study design. Four studies distinguished two groups in the study population according to the tumor type or radiation therapy technique [ 19 , 20 , 21 , 22 ]. Therefore, we divided these studies and analyzed the subgroups as separate study groups.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 29 studies reported the prevalence of retinopathy, including 2458 patients [ 1 , 7 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Of these 29 studies, 27.6% were sinonasal tumors, 21% were nasopharyngeal tumors, 13.8% were maxillary sinus carcinoma, 10% were optic nerve sheath meningioma, 6.9% were head/neck cancers, and 3.4% consisted of skull base meningioma, cavernous malformation, and olfactory tumors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations